INVESTIGATION OF ALTERNATIVE TOURISM TYPES AND SIGHTS VIA GEOGRAPHIC INFORMATION SYSTEMS: THE EXAPLE OF SAFRANBOLU - Fatih Aydın; Osman Çepni; Tuğba Turgut (Copernicus GmbH, 2017)
Abstract. In this study, alternative tourism types and sights belonging to Safranbolu were identified through Geographic Information System (GIS) tools. In this manner, most favorable tourism activities, which are specific to field, and evaluation factors of these activities were determined. “Suitability classification values” of these factors were charted by receiving opinions from experts. Natural and cultural properties of study area were determined in the light of evaluation factors and a database was set via GIS. This database was examined according to evaluation factors of the activities and the most suitable and conditional suitable areas were determined. In this study, it is aimed to carry out the suitable place analysis for alternative tourism types of Safranbolu, which is a tourism town, such as riding, mountain biking, camping, trekking. 486 km2 area for riding, 319 m2 for trekking, 209 km2 for mountain biking and 148 km² for camping were figured out as suitable. These results reveal that tourism activities should be more professionally organized in order to apply alternative tourism types such as riding, mountain biking, camping, trekking. In addition, organizations such as festivals and fairs should be arranged in order to introduce products special to Safranbolu.
Keywords: Cartography; Technology; Astronomy; Management, Monitoring, Policy and Law; Environmental science; Tourism; Agricultural and Biological Sciences; FOS: Economics and business; Engineering; Applied optics. Photonics; Business; Sustainable Management of Rangelands and Livestock; Environmental resource management; Order (exchange); Geography; T; Sight; Physics; Life Sciences; Land-Use Suitability Assessment Using GIS; Forestry; Transport engineering; Engineering (General). Civil engineering (General); GIS; TA1501-1820; Archaeology; Environmental Science; Physical Sciences; TA1-2040; Geographic information system; Finance; 11. Sustainability; 15. Life on land